(untitled) (Research, Society and Development, 2023)
Objective: To analyze the scientific evidence on the nursing diagnosis of sedentary lifestyle in high-risk pregnant women. This is an integrative literature review study using the descriptors nursing diagnosis, high-risk pregnant women and sedentary lifestyle. Carried out in the databases Scientific Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS), Medical Literature Analysis and Retrieval System Online (Medline). The final sample consisted of 11 original articles published in Portuguese and Spanish. Lack of physical exercise and inadequate nutrition were the most cited risk factors in addition to maternal cardiovascular risk, hypertension and gestational diabetes. However, it is expected that the actions developed by nurses in prenatal care can grow more and more.